Description of Selective Behavioral Experience of Choosing Covid-19 information In Mass Media Television - Maylanny Christin; Rico Kurnia Yudhaswara; Dasrun Hidayat (Jurnal Penelitian Komunikasi dan Opini Publik, 2021)
Television is one of the media that delivers information about COVID-19. In the midst of the COVID- 19 emergency, television deserves to be the foremost, quality and reliable source of information. Researchers are interested in researching how people experience selective behavior in choosing COVID-19 information in television mass media. The existence of selective behavior is expected by society to be able to reduce anxiety due to media exposure. The purpose of this study was to find out how the community experiences selective behavior in choosing information about COVID-19 on television media. The research used a descriptive- qualitative approach with the type of phenomenological research. Data collection techniques through interviews with 5 informants with criteria that have been determined by the researcher. The results of the study focus on the behavioral experiences of selectively selecting COVID-19 information including ensuring information is in accordance with needs, adjusting the frequency of accessing COVID-19 information, and cross-checking information from other sources. The results of this study are expected to have implications for the level of awareness of the importance of media literacy. Selective behavior reflects that the audience is smart in determining the appropriate media channels and content.